Review of Recent Works in Maturidi Theology: Maturidi Theology: A Bilingual Reader (by ejla Demiri, Philip Dorroll, Dale J. Correa, Eds.) and Transcendent God, Rational World: A Maturidi Theology (by Ramon Harvey) (American Journal of Islam and Society, 2023)
Within Islamic studies, the subfield of theology has been one of steady growth over the decades. With respect to the Māturīdī school of theology, indebted to the eponymous Abū Manṣūr al-Māturīdī (d. 333/944), a noticeable increase in publications, scholarly monographs, and peer-reviewed journal articles has appeared in recent years. Joining this expanding scholarly effort are the following two works: an Arabic-English reader entitled Māturīdī Theology edited by Lejla Demiri, Philip Dorroll, and Dale Correa and Ramon Harvey’s scholarly monograph Transcendent God, Rational World: A Māturīdī Theology, which is both analytical and constructive in its approach.